MENINGKATKAN KEPATUHAN WAJIB PAJAK DENGAN PEMERIKSAAN PAJAK, PENGETAHUAN PERPAJAKAN DAN PELAYANAN PEGAWAI PAJAK SEBAGAI PREDIKTOR PADA KPP PRATAMA MEDAN KOTA - AHMAD SANI; SITI ANISYAH (JURNAL ILMIAH KOHESI, 2020)
Tax is one of the biggest sources of state revenue to finance development activities. However, the low level of taxcompliance in meeting tax obligations in Indonesia especially KPP Pratama Medan Kota, the realization of tax revenue didnot reach the target set. The purpose of this study was to determine the effect of tax audits, tax knowledge and taxemployee services to improve taxpayer compliance. This research uses an associative approach with the number ofregistered taxpayers population and submits Annual Tax Return in KPP Pratama Medan Kota in 2016 as many as 61,758.The sampling technique uses a random sample with the Slovin formula and the number of samples is 100 respondents.Data sources using primary data and data collection techniques using surveys and literature. Data analysis techniques usedmultiple linear regression, which was previously tested for validity, reliability, classic assumption and hypothesis testing. Theresults showed that the tax audit did not significantly influence the compliance of individual taxpayers. Knowledge of taxationhas a significant effect on taxpayer compliance in KPP Pratama Medan Kota. Knowledge of taxation has a significant effecton taxpayer compliance in KPP Pratama Medan Kota. Tax audits, tax knowledge, and services of tax officers together havea significant effect on taxpayer compliance in KPP Pratama Medan Kota.